ENHANCEMENT OF SELF-ESTEEM OF EARLY STUDENTS WITH TEAM ACCELERATED INSTRUCTION (TAI) LEARNING METHODS - Ayunda Zahroh Harahap (BUHUTS AL-ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2022)
The ability of students to adapt to the campus environment or college adjustment is influenced by one important aspect that helps students succeed in the lecture environment, namely increasing self-esteem. Self-esteem is an important thing in one's life, it is closely related to the way humans are humans can see about their own situation. The PBAK program has not completely touched the important condition that individuals must possess properly, namely self-esteem. This fact is a concern for researchers to try to provide an intervention program to increase self-esteem for students majoring in PIAUD FTIK IAIN Padangsidimpuan, if students have low self-esteem, it will certainly increase their chances of experiencing failure in academic performance, which in turn will increase the level of distress. psychological well-being and will have a negative impact on their own personal circumstances. This research is a quasi-experimental or quasi-experimental study with a quantitative approach consisting of one experimental class. The purpose of this study was to obtain an overview of the use of TAI-type cooperative learning to increase students' self-esteem. To see whether there was an increase in students' logical thinking skills and also students' self-esteem. The condition of self-esteem of students who received Team-Accelerated Instruction (TAI) cooperative learning showed an improvement towards a better direction, meaning that the TAI learning model could be used to help develop personality such as self-esteem. One group pretest-posttest design was used.